THE LEGAL DILEMMA OF SURROGATE MOTHERHOOD: A COMPARATIVE PERSPECTIVE ON THE PROTECTION OF WOMB RENTAL IN INDONESIA AND THAILAND - Kusuma, Nadya Sandrina; Rahmi, Atikah Rahmi (International Journal of Cultural and Social Science, 2026)
The practice of surrogacy is one of the implications of reproductive technology developments that raises complex legal issues, particularly regarding the validity of agreements and the legal status of children born as a result. In Indonesia, this practice is not specifically regulated in legislation, creating legal uncertainty for the parties involved. This study aims to analyze the legal status of surrogacy agreements and their legal implications for the status of the child born according to the perspectives of Indonesian and Thai law. The research method used is normative legal research with a legislative and comparative law approach. Data were obtained through a literature study of primary, secondary, and tertiary legal materials, which were then analyzed qualitatively. The results show that in the Indonesian legal system, surrogacy agreements are considered contrary to the valid requirements for agreements in the Civil Code, the provisions of the Health Law, and the norms of morality and public order, and are therefore considered null and void. As a result, the legal status of children born from such practices is uncertain and they tend to be recognized only as the children of the woman who gave birth. In contrast, Thailand, through the Protection for Children Born through Assisted Reproductive Technologies Act B.E. 2558 (2015), has provided specific regulations that recognize surrogacy agreements under strict conditions and guarantee the legal status of children as legitimate children of the couple undergoing surrogacy. This study concludes that comprehensive legal regulations are needed in Indonesia to provide legal certainty and protection for the rights of children born through surrogacy practices.